ANALISIS TOKOH ALICIA BERENSON DALAM NOVEL THE SILENT PATIENT (PELUKIS BISU) KARYA ALEX MICHAELIDES - Thessa Delviani, Callista; Ervalia, Intan; Dwi Kurniawan, Eva (Institut Agama Islam Darussalam Blokagung Banyuwangi, 2024)
This research aims to dig up information and describe the main character in the novel The Silent Patient (The Silent Painter) by Alex Michaelides, namely Alicia Berenson, through Sigmund Freud's psychoanalytic approach, revealing the internal conflict in the personality structure of Alicia Berenson's character, which is reflected in the depiction of the Id through primitive drives. and unconscious instincts, the Ego in its efforts to balance the Id's needs with the reality of the outside world, and the Superego which contains moral values ??and social norms that influence Alicia's actions and behavior. This research uses a qualitative approach by observing the novel text in depth regarding the motives and behavior of the characters in this novel, and reviewing hidden psychological aspects through in-depth analysis of the storyline and interactions between characters. The results obtained from this research are that Alicia's id is reflected in her tragic act of killing her husband in an effort to satisfy her unconscious desires. Alicia's ego, as a balance between the Id and reality, appears in the psychotherapist's efforts to help Alicia speak again and respond to the reality around her. Meanwhile, Alicia's superego is reflected in her inner conflict between the desire to defend herself and guilt over her husband's death, which results in Alicia having difficulty speaking and expressing her traumatic emotions. The conclusion obtained in this research is that her Id was reflected in the tragic act of killing her husband, while her Ego and Superego played a role in healing efforts and inner conflicts related to feelings of guilt and self-defense for this incident.